Analysis of Intrinsic Elements in New Prose From Gudrun and Susan Ray - Tarigan, Emiya Endima; Harahap, Ahmad Bengar (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to analyze the intrinsic elements of Gudrun and Susan Ray's latest prose. This paper is a literary research that uses a descriptive qualitative method. The data of this study refers to intrinsic elements. The source of data for this research is present-day prose by Gudrun and Susan Ray. The results of the study show that intrinsic elements are inherent in the theory of structuralism. Using Marquass theory, the intrinsic elements are categorized into 4, namely plot, characters, setting, point of view. Based on this study, the author recommends that the results of the analysis of intrinsic elements can be applied in the current literature courses, especially to enrich the curriculum related to literature. This can help increase understanding and appreciation in the Contemporary Literature course.